2021
DOI: 10.3389/fimmu.2021.623973
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell-Derived Extracellular Vesicles Regulate the Mitochondrial Metabolism via Transfer of miRNAs

Abstract: Mesenchymal stromal cells (MSCs) are the most commonly tested adult progenitor cells in regenerative medicine. They stimulate tissue repair primarily through the secretion of immune-regulatory and pro-regenerative factors. There is increasing evidence that most of these factors are carried on extracellular vesicles (EVs) that are released by MSCs, either spontaneously or after activation. Exosomes and microvesicles are the most investigated types of EVs that act through uptake by target cells and cargo release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 117 publications
0
24
0
Order By: Relevance
“…On the other hand, it has been called that one of the elements of the damaged system was damage to its energetics, which are miraculously restored with the addition of stem cells or derived vesicles [38][39][40][41][42]. Again, it followed from straightforward logic that elements of the energy system, in particular mitochondria, were delivered to the affected system, which by their activity were designed to repair the damaged energy exchange, followed by the full functioning of the targeted cell and organ, as a result of which a search was undertaken for the presence of mitochondria in vesicles.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…On the other hand, it has been called that one of the elements of the damaged system was damage to its energetics, which are miraculously restored with the addition of stem cells or derived vesicles [38][39][40][41][42]. Again, it followed from straightforward logic that elements of the energy system, in particular mitochondria, were delivered to the affected system, which by their activity were designed to repair the damaged energy exchange, followed by the full functioning of the targeted cell and organ, as a result of which a search was undertaken for the presence of mitochondria in vesicles.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…A possible method to resolve this issue is to overexpress therapeutic molecules, such as mRNAs, miRNAs, or proteins, in MSC-derived EVs and produce a large number of EVs encapsulating these molecules. In fact, it has been shown that cells overexpressing certain miRNAs secrete EVs containing abundant miRNAs [ 249 , 250 , 251 ]. In addition, an approach that completely improves the therapeutic effect of MSC-derived EVs would be to produce a large number of EVs containing an excess of molecules by inducing a specific stimulus to the MSCs with the target therapeutic effects.…”
Section: Therapy Via Msc-derived Evs As a Novel Dds Systemmentioning
confidence: 99%
“…This effect can be enhanced by combining MSC-EVs with chemotherapeutic agents [219,220]. Although the underlying molecular mechanisms remain unexplored, this effect could be mediated by miRNA cargo as MSC-EV miRNA has been shown to modulate pathways involved in mitochondrial function [216,221]. Furthermore, this mitochondria-mediated therapeutic action is not limited to apoptosis.…”
Section: Naturally Occurring Evsmentioning
confidence: 99%